2002
DOI: 10.1021/la015592t
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bowl-Shaped Morphology of Crew-Cut Aggregates from Amphiphilic Block Copolymers of Styrene and 5-(N,N-Diethylamino)isoprene

Abstract: A new morphology of crew-cut aggregates prepared from highly asymmetric triblock copolymers of 5-(N,N-diethylamino)isoprene and styrene in dilute solution is reported. After quaternization of the polar block, using dimethyl sulfate, the copolymers consist of a long block of polystyrene (PS) with short poly[5-(N,N,N-diethylmethylammonium)isoprene] (PAI) blocks at both chain ends. The aggregates were prepared by first dissolving the copolymers in a common solvent for both blocks and then adding water to induce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(156 citation statements)
references
References 34 publications
7
148
1
Order By: Relevance
“…In neutral aqueous solutions, this star self-assembled forming spherical aggregates coexisting with bowl shaped morphologies, due to a possible viscosity control mechanism. The bowl-like morphology has been reported by Eisenberg et al for linear copolymers [41]. This was the first time that such morphology was observed in the aggregation of star block copolymers.…”
Section: (Ab) N Star Block Copolymerssupporting
confidence: 70%
“…In neutral aqueous solutions, this star self-assembled forming spherical aggregates coexisting with bowl shaped morphologies, due to a possible viscosity control mechanism. The bowl-like morphology has been reported by Eisenberg et al for linear copolymers [41]. This was the first time that such morphology was observed in the aggregation of star block copolymers.…”
Section: (Ab) N Star Block Copolymerssupporting
confidence: 70%
“…More information about these nonclassical vesicle structures can be found in a review by Burke et al, 54 and a brief summary (including vesicle sizes) and additional references are given in Table 2. Recently, Riegel et al 55 observed a bowl-shaped morphology from triblock copolymers [5- 11 -PS 228 -b-PAI 11 )] in THF/water or dioxane/water mixtures. They showed that these structures, which had some similarity to vesicles although they were not unilamellar structures, were only kinetically stable and not under equilibrium control.…”
Section: Other Bilayer Morphologiesmentioning
confidence: 99%
“…[25][26][27] The porous spheres of PS-b-PAA and PS-b-PEO BCPs were encountered only under some preparative conditions. 25 A bowl-like structure was prepared from 5-(N,N,Ndiethylmethylammonium)isoprene and styrene triBCPs (PAIb-PS-b-PAI) in dilute solution.…”
Section: Communicationmentioning
confidence: 99%
“…26 It has been found that the internal viscosity and the rate of water addition are the main factors for the formation of bowl-shaped structure or porous spheres. 26 Jiang et al reported bowl and dimpled shape supramolecular assemblies from mono-component polyimide. 28 Recently bowl-and porous sphere-shaped supramolecular assemblies were prepared by self-assembly of a supramolecular copolymer which was formed through end group ionic interaction between hydrophilic poly(2-methacryloyloxyethyl phosphorylcholine) with amino end groups (PMPC-NH 2 ) and hydrophobic polystyrene with carboxyl end groups (PSt-COOH).…”
Section: Communicationmentioning
confidence: 99%